1469. Microbial Etiology of Community-Acquired Pneumonia Requiring Hospitalization Among US Adults. (26th November 2018) - Deshpande, Abhishek; Richter, Sandra S; Haessler, Sarah; Yu, Pei-Chun; Imrey, Peter; Rothberg, Michael
Abstract: Background: Community-acquired pneumonia (CAP) continues to be the leading cause of infection-related mortality in the United States. Epidemiological studies of CAP are usually based on single-center studies and there is a need for large population based studies. We evaluated the microbial etiology of CAP among patients requiring hospitalization using a large US database. Methods: We included adult patients admitted with pneumonia from 2010 to 2015 to 175 US hospitals participating in Premier and providing administrative and microbacteriological data. Patients were identified as having CAP if they had a radiographic evidence of pneumonia (X-ray) on the first day and if they were on antimicrobials on the first day for 3 consecutive days. For studying the microbial etiology, patients were included if they had a positive culture or test collected by hospital Day 0 or 1. Patients with identical Gram negative organisms in blood and urine were excluded. We also excluded patients with a present on admission secondary diagnosis of cholecystitis, appendicitis, peritonitis or abdominal infections. Results: A total of 95, 169 patients had a diagnosis of CAP with a culture or other test performed on the first day. A pathogen was detected in 15.4% of the patients. Among the pathogen positive patients, the mean age was 67 ± 16 years (range 18–89) and 52% were male. Thirty-four percent required ICU care and 8.4% died in the hospital. Almost all patients (99%) had at least one culture drawn, including blood (96%) and respiratory (51%) specimens. Bacteria were the most commonly detected pathogens. Among the Gram-positive bacteria, Streptococcus pneumoniae accounted for 22.2% followed by methicillin sensitive Staphylococcus aureus (MSSA) (14.8%) and methicillin-resistant S. aureus (7.9%). Among the Gram-negative bacteria, the most common organisms reported were Pseudomonas aeruginosa (5.9%), Escherichia coli (5.2%) and Hemophilus influenzae (5.3%). Mycoplasma pneumoniae was identified in 2.2%. Among viral pathogens, the most common were influenza virus (2.6%) and human rhinovirus (0.71%). Conclusion: In a large US inpatient sample, a majority of patients with CAP had no microbial etiology identified by laboratory testing. Among the test positive patients, S. pneumoniae was the most common bacteria reported followed by MSSA and MRSA. Disclosures: A. Deshpande, 3M: Investigator, Research support; Clorox: Investigator and Speaker's Bureau, Research grant and Speaker honorarium; Merck: Investigator and Speaker's Bureau, Research support. S. S. Richter, bioMerieux: Grant Investigator, Research grant; BD Diagnostics: Grant Investigator, Research grant; Roche: Grant Investigator, Research grant; Hologic: Grant Investigator, Research grant; Diasorin: Grant Investigator, Research grant; Accelerate: Grant Investigator, Research grant; Biofire: Grant Investigator, Research grant.